Factors Affecting Public Employees’ Acceptance of Video Conferencing Tools: An Extended TAM Perspective - Baki Bulduk; Erhan Ünal (Open Praxis)
This study aimed to explore the key determinants of public employees’ acceptance of video conferencing tools (VCTs) using the Extended Technology Acceptance Model. In addition to the core TAM constructs—perceived usefulness, perceived ease of use, attitude, and behavioral intention—subjective norms, output quality, technostress, self-efficacy, facilitating conditions, technological complexity, and perceived enjoyment were selected for the study. A cross-sectional survey design was employed, using a convenience sampling method to select a study sample of 240 participants working in different public institutions. Following the removal of seven incomplete survey responses, a total of 233 valid responses were analyzed. The study’s results empirically confirmed that attitude and perceived usefulness played significant roles in predicting behavioral intention to use VCTs. Additionally, the results reflected significant correlations between perceived usefulness and output quality, perceived usefulness, and subjective norms. Additionally, the study also demonstrated that self-efficacy, perceived enjoyment, facilitating conditions, and technological complexity predicted perceived ease of use. Overall, the results indicated that the study’s proposed model, which included external constructs, was satisfactory in explaining public employees’ acceptance of VCTs. As such, the study can be said to have enriched the knowledge about technology acceptance and offers implications for the use of VCTs in the future.